Strategi usaha tambak ikan bandeng (Chanos chanos) di Desa Bipolo Kecamatan Sulamu - Erwindo, Vanesa Yan; Dahoklory, Nicodemus; Sunadji, Sunadji (Jurnal Aquatik, 2022)
This research aims to find out the business strategy of milkfish ponds (Chanos chanos) in Bipolo Village of Sulamu Subdistrict. This research was conducted for a period of 1 (one) month, in the Bipolo Village Area of Sulamu Subdistrict with the number of research samples as many as 13 people who worked as bandeng pond cultivators in Bipolo Village. The methods used in this study in the form of interviews, observations, documentation, and analysis are used, namely SWOT analysis. From the results of the study showed that the business development strategy with SWOT analysis lies in quadrant I. That is, it has progressive strengths and opportunities using so (Strength Opportunities) strategy. The strategies used are the management of natural resources and increasing the capacity of human resources to maximize the quantity and quality of production of bandeng fish, conducting market analysis to determine the production cycle of milkfish. The results of the SWOT matrix recommend that the strategy for the development of milkfish enlargement business is to maximize existing resources by increasing the capacity of pond farmers to milkfish enlargement techniques. Keywords: Milkfish Pond Bussines, Strategy, SWOT Analysis